Distribution of dissolved trace elements in the Laptev Sea affected by the Lena River discharge; Marine Pollution Bulletin; Vol. 202 - Moiseeva Yu. A. Yuliya Aleksandrovna; Purgina D. V. Dariya Valerievna; Pipko I. I. Irina Ivanovna; Guseva N. V. Natalia Vladimirovna; Gershelis E. V. Elena Vladimirovna; Khvaschevskaya A. A. Albina Anatolievna; Pugach S. P. Svetlana Petrovna; Yakushev E. V. Evgeny Vladimirovich; Semiletov I. P. Igor Petrovich (2024, 2024)
Title screen